Modeling international diffusion: Inferential benefits and methodological challenges, with an application to international tax competition - Robert J. Franzese; Jude C. Hays (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
Although scholars recognize that time-series-cross-section data typically correlate across both time and space, they tend to model temporal dependence directly, often by lags of dependent variables, but to address spatial interdependence solely as a nuisance to be “corrected” by FGLS or to which to be “robust” in standard-error estimation (by PCSE). We explore the inferential benefits and methodological challenges of directly modeling international diffusion, one form of spatial dependence. To this end, we first identify two substantive classes of modern comparative-and-international-political-economy (C&IPE) theoretical models—(context-conditional) open-economy comparative political-economy (CPE) models and international political-economy (IPE) models, which imply diffusion (along with predecessors, closed-economy CPE and orthogonal open-economy CPE)—and then we evaluate the relative performance of three estimators—non-spatial OLS, spatial OLS, and spatial 2SLS—for analyzing empirical models corresponding to these two modern alternative theoretical visions from spatially interdependent data. Finally, we offer a substantive application of the spatial 2SLS approach in what we call a spatial error-correction model of international tax competition. – – Obwohl Wissenschaftler wissen, dass Zeitreihenquerschnittsdaten sowohl über die Zeit als auch über den Raum korreliert sind, neigen sie dazu, die zeitliche Abhängigkeit direkt zu modellieren, z. B. durch Zeitabstände der abhängigen Variablen. Die räumliche Abhängigkeit jedoch wird als ein Ärgernis angesehen, welches durch FGLS ,korrigiert' wird oder ,robust' gemacht wird in Standard- Abweichungs-Schätzungen (durch PCSE). Wir untersuchen methodologische Herausforderungen und die Nutzen für Schlussfolgerungen aus einer direkten Modellierung internationaler Diffusion als einer Form der räumlichen Abhängigkeit. Zu diesem Zweck identifizieren wir zuerst zwei inhaltliche Hauptklassen theoretischer Modelle der modernen ,Vergleichenden und Internationalen Politischen Ökonomie“, nämlich Modelle der (kontextbezogenen) Vergleichenden Politischen Ökonomie Offener Volkwirtschaften und Modelle der Internationalen Politischen Ökonomie. Diese bilden Diffusion ab, ebenso wie die Vorläufermodelle der Vergleichenden Politischen Ökonomie geschlossener Volkswirtschaften und gegensätzlich offener Volkswirtschaften. Zweitens bewerten wir die relative Performanz von drei Schätzern – nicht-räumliche OLS, räumliche OLS und räumliche 2SLS. Schließlich wenden wir den Ansatz des räumlichen 2SLS in einem von uns so genannten ,Spatial Error Correction'-Modell des internationalen Steuerwettbewerbs an.
Keywords: C23; H20; 330; International Tax Competition; Panel Models; Policy Diffusion; Political Economy; Spatial Interdependence